Minimally Invasive Mitral Valve Repair in a Marfan Patient with Severe Scoliokyphosis - Noack, Thilo; Lehmkuhl, Lukas; Seeburger, Joerg; Mohr, Friedrich Wilhelm (The Thoracic and Cardiovascular Surgeon Reports, 2014)
A 26-year-old female Marfan patient with extensive scoliokyphosis presented with severe mitral valve regurgitation. The patient was treated with minimally invasive mitral valve repair via a right lateral minithoracotomy. In this report, we discuss the operative procedure followed in this special case and the current literature.
Keywords: mitral valve regurgitation; minimally invasive mitral valve repair; minithoracotomy; scoliokyphosis